2022
DOI: 10.1242/jcs.259980
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Num1-mediated cortical dynein anchoring negatively impacts respiratory growth

Abstract: Num1 is a multifunctional protein that both tethers mitochondria to the plasma membrane and anchors dynein to the cell cortex during nuclear inheritance. Previous work has examined the impact loss of Num1-based mitochondrial tethering has on dynein function in Saccharomyces cerevisiae; here, we elucidate its impact on mitochondrial function. We find that like mitochondria, Num1 is regulated by changes in metabolic state, with the protein levels and cortical distribution of Num1 differing between fermentative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Our previous study demonstrated that ​​Num1-mediated cortical dynein anchoring is important for normal growth under respiratory conditions ( White et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study demonstrated that ​​Num1-mediated cortical dynein anchoring is important for normal growth under respiratory conditions ( White et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…We refer to this artificial mitochondria-PM tether as RID-Mdv1 ( Figure 6A ). RID-Mdv1 is an inducible version of a constitutive Mdv1NTE-Pil1 artificial tether we used previously to test whether restoring contact or proximity between mitochondria and the PM was able to rescue the respiratory growth defect of ∆ num1 cells ( White et al. , 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans samples were spotted with 5 μL on plates containing different carbon sources and stress reagents, and then incubated at various temperatures for 48 h to observe growth. In addition, we diluted cells to 300 cells/mL in PBS, applied 100 μL to YPD and YPEG solid medium, and incubated at 30 °C, 35 °C, and 37 °C for 48 h [ 23 ]. Colony size was measured with vernier calipers at the end of the incubation.…”
Section: Methodsmentioning
confidence: 99%